2008
DOI: 10.1111/j.1365-2958.2008.06191.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycothiol regulates and is regulated by a thiol‐specific antisigma factor RsrA and σR in Streptomyces coelicolor

Abstract: SummaryMycothiol (MSH) is a small thiol molecule with a cysteine-ligated disaccharide structure found in actinomycetes that include streptomycetes and mycobacteria. In Streptomyces coelicolor, a model organism for antibiotic production and differentiation, the amount of MSH is under the control of a sigma factor s R , which is regulated by an antisigma factor RsrA with a thiol-disulphide redox switch. We found that the first gene (mshA) in the biosynthetic pathway for MSH and the gene for amidase (mca) that pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
111
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(115 citation statements)
references
References 35 publications
4
111
0
Order By: Relevance
“…When MSH levels were examined in a R -deficient mutant, they were fourfold lower than parental levels during all phases of growth. More recently, the role of R in MSH metabolism was elaborated by Park and Roe (106). A complex is formed between R and the reduced form of the R regulator.…”
Section: Regulation Of Msh Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…When MSH levels were examined in a R -deficient mutant, they were fourfold lower than parental levels during all phases of growth. More recently, the role of R in MSH metabolism was elaborated by Park and Roe (106). A complex is formed between R and the reduced form of the R regulator.…”
Section: Regulation Of Msh Biosynthesismentioning
confidence: 99%
“…R activates direct expression of a host of genes, including mshA and mca, and indirect expression of mshB, mshC, and mshD (106). Treatment of cells with reagents that deplete MSH, including the thiol oxidant diamide and the thiol alkylating agents monobromobimane (mBBr) and N-ethylmaleimide, leads to oxidation of RsrA and the release of R , with subsequent expression of the R regulon.…”
Section: Regulation Of Msh Biosynthesismentioning
confidence: 99%
“…In its reduced state, an anti-s R , RsrA, will sequester the sigma factor and prevent its interaction with the RNA polymerase. Under conditions of thiol stress, two cysteine residues in the RsrA will be oxidized, causing the dissociation of the s R , which will induce its regulon including the mshA gene (Park & Roe, 2008). Moreover, it was shown that MSH is the biological reductant that modulates RsrA activity, suggesting that the RsrA-s R system is a sensor for MSH levels in the cell (Park & Roe, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The induction of BSH biosynthesis genes is analogous to the stress-responsive induction of MSH synthesis in the actinomycetes. MSH production in Streptomyces coelicolor is under the regulation of the general stress sigma factor, s B (Lee et al, 2005) and the thiol-oxidative stress responsive sigma factor, s R (Park & Roe, 2008). In its reduced state, an anti-s R , RsrA, will sequester the sigma factor and prevent its interaction with the RNA polymerase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation